Analisis Kesiapsiagaan Bencana Pada Guru Sekolah Dasar - Syahrial Ayub; Muh. Makhrus; I Wayan Gunada; Muhammad Taufik (Postgraduate, University of Mataram, 2020)
The purpose of this study was to determine the level of teacher preparedness in primary schools against natural disasters. The research sample was 15 teachers from SD N 6 Mataram. Data collection is done through questionnaires consisting of 5 aspects of disaster, knowledge and signs, impacts, risks and efforts to reduce, preparedness and procedures and first aid tools for victims. We results obtained are (1) knowledge and signs of the occurrence of disasters are in the less category (56.11%). (2) the impact caused if a disaster occurs is in the less category (49.33%). (3) Risk and efforts to reduce disaster risk in the good category (73.33%). (4) Disaster preparedness in the good category (79.05%), and (5) victim first aid procedures and tools in the less category (53.33%). Based on the results, it can be concluded that the level of preparedness of teachers in facing disasters in SD Negeri 6 Mataram is in the sufficient category of 61.71%. Therefore, socialization and knowledge related to disaster preparedness for teachers in primary schools need to be improved